Development of an Intelligent Decision Support System For Flood Mitigation in Pahang River - Wan Faizal, Wan Ishak; Saher, Faisal Nadeem; Nasly, Mohamed Ali; Mohd Abdul Nassir, Bidin (2014)
This is an established truth that with the growing world, the flood hazards cannot be avoided but the technology is a solution to minimize this process. A sustainable development depends on plans, which are designed on the strong basis of comprehensive datasets. Managing river is an acute and more attentive area where it faces heavy water feeds due to rains. Malaysia is going on fast development including infrastructural developments and change of land uses from forest cover to other non-green land uses. Adopting innovative products for flood mitigation are required as an integral part of local design transformation. Keeping this fact in view, the vulnerability which may cause due to floods in Pahang River seems to be a threat for the sustainable development of the area. The general objective of this study was to propose a visual aided decision support platform providing an ease but acceptable level of strategy. Presented prototype includes modelling and GIS based visual aids. A study of Pahang River in Malaysia conducted, to explain the applications of the prototype. To achieve this goal a geodatabase, consisting of different hydro-informatics data layers, has been developed. Further work on modified models for better forecasting under real time data input and design of innovative selfprotecting flood mitigation at industrial and house hold level is identified as future research area. Under this research studies, the required datasets were generated using remote sensing and GIS system integrated with field GPS surveys. The methodology adopted to achieve the desired goals and to combat the complexity of the hydrogeodatabase of Pahang River drawn from the idea to integrate the engineering tools with the geo-informatics techniques. This resultant output of the project enabled to develop a system for the existing and future development datasets in different research institutions in Malaysia for the decision makers and researchers. This hydro-geodatabase is GISbased and primarily data driven. The proposed 3d visual aided platform for decision functions is the salient feature of this research study. Flood hazards caused by extreme rain events or unplanned watersheds is a problem and it has become a growing concern under impact of climate change. There is a dire need to develop new paradigm to combat flood hazards and operational decision making process. Effective decision is a challenge, in a context to select best-suited option for mitigation. This study affirms two major conclusions: First, there is a great potential to adapt the proposed methodology at the level of decision-making authorities, leading to selection of actual measures for flood mitigation. Second, integration of model, Water Evaluation and Planning (WEAP), Global Mapper and GIS proved as a salient feature of Decision Support System as visual aided scenario generation. This study has given an account of and the reasons for the use of prototype for flood hazards. Contemporary challenge for Pahang River is its computer aided management and future challenges include sustainable flood mitigation master plan under innovative fashion. Tools of hydroinformatics like simulation modelling, information handling and data communication under the environment of GIS has been proving its worth since last two decades. Implementation of these tools to strengthen flood forecasting and warning system would prove an effective way for emergency responses. This aspect covers informatics but on the other hand some structural efforts and plans are required for mitigation process. This study has also focused on improved and intra-institutional network of information sharing as a platform of decision making for authorities. It is concluded that adopting the tools of hydroinformatics and computer aided river management (CARM) would be considered to be best option with continued process of fine tuning the informatics resources.